Entre utilitarisme et pessimisme : pour une recherche utile, utilisable et utilisée - Jean-Philippe Tonneau (Éditions en environnement VertigO, 2012)
There is no day without a book, a debate, a declaration underling the limits of our development : economic limits, ecological limits, and social limits. The growth never creates enough jobs. Global warming is becoming real for everyone. Pollution multiplies and poses public health problems. Exclusion, even if misery is, of course, more present in the South, is happening everywhere. However, science has never been so productive in knowledge and technology. But in spite of these technologies, we observe that the "wrong development" and its demonstrations (resources crisis, industrial pollution, misery, exclusion…) are always present. This is a paradox as science has never been so attentive to social request and so worried by its “utility”. The expression “social request” suggests that actors external to the scientific community should contribute to the definition of the research problems (Grossetti, 2000). Gibbons et al. (1994) defend the assumption of a new method of knowledge production, focused on the problems to solve as they are defined by industry or the public authorities, in rupture with the academic organization of disciplines and universities. These choices result in a “useful” research, even utilitarian, conceived for its applications, but without real capacities to think towards the future. The authors defend the idea that the future is so uncertain that science cannot be fully mobilized. They justify this assumption by showing the insufficiency of the answers to the challenges of sustainable development and by underlining the low capacity of innovation of the society to face changes. Using the concept of “capacity of adaptation” developed within the reflection on the climate change, they propose the adaptation of the processes of innovation in company to sustainable development through training processes and competences reinforcement. They recommend a “citizen” research enlightening the actors choices. They insist and detail on the main roles of this research : social experimentation and information management to work out at the same time a society project and to develop the answers that this project requires.